With a little help from my friends: physiological integration facilitates invasion of wetland grass Elymus athericus into flooded soils. Issue 3 (24th December 2020) - Mueller, Peter; Do, Hai T.; Smit, Christian; Reisdorff, Christoph; Jensen, Kai; Nolte, Stefanie
Abstract : Tidal wetlands worldwide are undergoing rapid invasions by tall‐growing clonal grasses. Prominent examples are invasions by species of the genera Spartina, Phragmites and Elymus . The responsible physiological and ecological drivers of these invasions are poorly understood. Physiological integration (PI) is a key trait of clonal plants, which enables the exchange of resources among ramets. We investigated PI in Elymus athericus, which has been rapidly spreading from high‐marsh into low‐marsh environments of European salt marshes during the last decades. We applied a nitrogen stable‐isotope approach to trace nutrient translocation between ramets in a factorial mesocosm experiment. The experiment was set up to mimic an invasion pattern commonly found in tidal wetlands, i.e. from high‐elevated and rarely flooded into low‐elevated and frequently flooded microenvironments. We tested for intraspecific variability in PI by including two genotypes of Elymus that naturally occur at different elevations within the tidal frame, a high‐marsh (HM) and a low‐marsh (LM) genotype. PI strongly increased offspring ramet aboveground and belowground biomass by 62 and 81%, respectively. Offspring ramets under drained conditions had 95% greater belowground biomass than those under flooded conditions. LM genotype offspring ramets produced 27% more aboveground biomass than HM genotypes. Offspring ramets were clearly more enriched in 15 N under flooded versus drained conditions; however, this positive effect of flooding on δ 15 N was only significant in the LM genotype. Our findings demonstrate the importance of PI for the growth of Elymus offspring ramets and thereby for the species' capacity for fast vegetative spread. We show that offspring ramets under stressful flooded conditions are more dependent on nutrient supply from parent ramets than those under drained conditions. Our data furthermore suggest a higher degree of adaptation to flooding via PI in the LM versus HM genotype. In conclusion, we highlight the importance of assessing PI and intraspecific trait variability to understand invasion processes within ecosystems.